Alkyl ethoxylate assisted liquid phase exfoliation of BN nanosheet and its application as interphase for oxide/oxide composites - Du, Zehui (2020)
An environment-friendly liquid phase exfoliation method assisted with alkyl ethoxylate wetting agent has been developed to prepare highly concentrated hexagonal boron nitride nanosheet (BNNS) colloidal suspensions with loadings of up to ~ 36.3 mg/mL. The exfoliation yield reaches ~78.3%. BNNS as thin as ~0.7–11.3 nm has been obtained and it retains pristine in-plane crystal structure without chemical bonds to alkyl ethoxylate. The obtained BNNS has been successfully applied to oxide/oxide ceramic composites (SiO2f/SiO2) as an interphase layer between fiber and matrix. The composites with BNNS generally exhibit non-catastrophic failure behaviour with the flexural strength of ~ 40–50 MPa and fracture toughness of ~ 1.68 MPa m1/2 which is about 50% higher than that of the composites without BNNS interphase. The effect of the BNNS interphase thickness on the mechanical properties of the composites has been studied and the role of BNNS in the toughness enhancement has been discussed. Furthermore, thermal stability of the BNNS interphase against prolonged heat treatment has been examined. Our alkyl ethoxylate assisted liquid phase exfoliation method paves a way for the applications of BNNS in various electronic or optical devices and also for the synthesis of nanocomposites.